Inovasi Pelayanan Kesehatan Jiwa dari Perspektif New Public Service (Studi Kasus Inovasi AKSI LILIN Kabupaten Lebak) - Adhityo Nugraha Barsei; Nova Yulanda Putri Sipahutar; Antonius Galih Prasetyo; Virgiawan Listanto (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
Mental health condition in Indonesia is in an alarming position. The study found that high prevalence of severe mental disorders such as schizophrenia in Indonesia. Unfortunately, people were less aware of several things that may cause mental health problems. Moreover, people with mental disorders were found to be reluctant or delaying treatment. In dealing with those various problems, the primary healthcare service as the front line in mental health services must carry out activities that are not business as usual. As a response to the mental health problems, Aksi Lilin (Ajak/inviting, Interaksi/ interacting, Lindungi/ protecting, Sayangi dengan Nurani/ loving) mental healthcare innovation was formed and implemented by the Primary healthcare Mandala in Lebak Regency. This study aims to explain and analyze the conditions of Aksi Lilin's innovation so it can be appropriately implemented. Furthermore, this study analyze innovation from the new public service perspective. This study uses a case study to analyze the implementation of Aksi Lilin innovation. Incentives, autonomy, leadership and culture, and enablers are the conditions to innovate. Aksi Lilin performs the NPS principles through mental health cadre participation. This study revealed that citizen participation through mental health cadres is crucial because primary healthcare has limited resources in providing public services. Moreover, the presence of the Aksi Lilin innovation is not only to meet service targets but also to realize that the government's task is to provide the best service to citizens, especially to vulnerable groups such as people with severe mental disorders.